GRACE: Girls Rising Above Circumstances to Excel. - Mims, Lauren. (2017)
Abstract: Black American adolescents are in a more vulnerable system than their white counterparts due to a persistent gap in wealth, high poverty, access to resources, overrepresentation in the prison-industrial complex, and other factors that perpetuate structural oppression and hinder achievement. This study describes the results of Girls Rising Above Circumstances to Excel (GRACE), an eight-week program developed specifically for 10th and 11th grade black girls. The once weekly eight-week program used group and individual activities to emphasize the importance of historical, ecological, and phenomenological contexts. Using surveys, this study examined patterns in self-perception, racial identity and achievement for a small cohort of students (N=10), both before and after the eight-week session. Results indicated that participant scores in self-perception, racial identity, and academic achievement improved. Findings can be used to support implementation of programs and policies that give black adolescent girls the tools they need to rise above circumstances to excel.; Thesis (M.A.)--Tufts University, 2014.; Submitted to the Dept. of Child Development.; Advisor: Ellen Pinderhughes.; Committee: Tama Leventhal, and Karen Craddock.; Keywords: Education, African American studies, and Developmental psychology.